Retail Investor Behavior, Cryptocurrencies, and Financial Market Innovation – Insights from the 5th European Retail Investment Conference (ERIC) - Hans-Peter Burghof; Achim Fecker; Patrick Jaquart; Benedikt Notheisen (Credit and Capital Markets – Kredit und Kapital, 2020)
The 5th European Retail Investment Conference was hosted at Börse Stuttgart, Germany, from April 10th to 12th 2019. The conference chairs invited academics and practitioners to participate and discuss empirical and theoretical research focusing on retail investor products and services, the impact of technology on retail investors, investors' decision-making, investor protection schemes, and market microstructure. Albert Menkveld, Professor of Finance at Vrije Universiteit Amsterdam and Fellow at the Tinbergen Institute, held the keynote about the fundamental value of bitcoin.
Keywords: 330